POTRET INDEKS KEPUASAN BIDAN TERHADAP PELAYANAN PUBLIK DI KABUPATEN BULELENG - Kadek Ayu Suarmini; Nyoman Mandayani; Ketut Siya Darmini; I Gede Purnawaman; I Nyoman Subanda (Jurnal Kesehatan Medika Udayana, 2020)
Backgroud: Public services perfomed by government officials in various sectors at this time are still found weaknesses. Weaknesses that occur when providing public services certainly have an impact on the quality of services received by the community. One of the public services performed by professional organizations is carried out by the branch manager of the Indonesian Midwives Association (IBI), Buleleng Regency. As for the form of public service provided is the management and extension of the midwife registration certificate (STRB) for the midwife. Purpose: The purpose of this study is to measure the midwife satisfaction index of public services conducted by the branch manager of the Indonesian midwives’ branch of the Buleleng branch. Method: The research design used is descriptive research. The population in this study were all members of STRB. The sampling technique used is probability sampling technique with simple random sampling. Data collection techniques using a questionnaire with 14 closed questions. The questionnaire was distributed through WhatsApp IBI Buleleng group by providing a link for filling out the questionnaire on google form. Result: The results of this study of the 14 elements are almost entirely namely 13 elements that are in the good category and only one element that is in the category of not good enough category in the speed of service. Conclusion: Thus, it can be concluded that the portrait of the midwife satisfaction index of public services in the Buleleng Regency is in the good category, so it can be said that the quality of the services of the IBI PC on the Buleleng Regency is also in the good category.Keywords: Administration; Midwife; Society Satisfaction Index; Public Services